Impacts of gluten aggregation behavior on the gassing properties of steamed bread during the wheat flour post-ripening - Zhang, Meng-Li; Guo, Xiao-Na; Sun, Xiao-Hong; Zhu, Ke-Xue (Food hydrocolloids, 2026)
This study aimed to provide novel insights into how wheat flour post-ripening influences steamed bread quality by systematically uncovering the relationship between gluten aggregation and gas retention properties. The results indicated that wheat flour post-ripening endowed the dough with excellent viscoelasticity and resistance to stress deformation, effectively maintaining the gluten network's ability to encapsulate gas. The steamed bread made from post-ripened wheat flour was more upright (height-to-diameter ratio increased from 0.58 to 0.66), with a decreased average cell area and increased cell density, especially after post-ripening at 38 °C. Post-ripening improved the gas retention rate of the dough, increased the rupture time (from 18.68 min to 24.27 min), and enhanced the rupture volume (from 0.96 mL/g to 1.02 mL/g). Wheat flour post-ripening promoted gluten polymerization (increased glutenin macropolymer content and decreased free sulfhydryl content and SDS-soluble protein), which was mainly reflected in the changes of α-, γ-gliadins, and B/C-LMW-GS subunits. The enhanced gas retention capacity was the primary factor contributing to the improvement in steamed bread quality, closely related to gluten aggregation behavior during the post-ripening of wheat flour. [Display omitted] •High temperature (38 °C) accelerated dough viscoelasticity and deformation resistance.•Wheat flour post-ripening improved the gas cell structure of steamed bread.•Post-ripening promoted protein cross-linking to enhance gas retention capacity.•The heat-induced cross-linking of proteins was higher in post-ripened wheat flour.•Correlation analysis revealed regulation of post-ripening on steamed bread qualities.